Metaevaluation of world bank evaluations of poverty reduction interventions in Uganda - Wandwasi, Peter Misigalo (My University, 2017)
Metaevaluation (evaluation of evaluations) contributes significantly in clarifying and resolving evident causes of inconsistencies in the evaluation outcomes, and enhances the effectiveness of development interventions. It is a specialised form of evaluation, which helps in judging the strengths and weaknesses of a primary evaluation so that interested parties in the intervention are able to judge the reliability and credibility of an evaluation and the evidence used to make decisions. The problem this research sought to solve was that, whilst it was evident that the majority of poverty-reduction interventions funded by the World Bank through its Poverty Reduction Support Credits (PRSCs) in Uganda had been systematically evaluated in order to measure their effectiveness, there was overall evidence of remarkable inconsistencies in the evaluation outcomes of the effectiveness of these poverty-reduction interventions in Uganda. Using four selected evaluation cases of poverty-reduction interventions of the World Bank, funded through its PRSCs and mixed methods approach (case studies, document analysis and descriptive frequency statistics) based on the Program Evaluation Standards (PES) developed by the Joint Committee in 1994, the main task of the research was to assess how effectively these selected evaluations met the requirements of a good evaluation in order to clarify and resolve evident causes of such inconsistencies. The theoretical basis for good programme evaluation upon which this thesis was based is driven mainly by the quest to promote accountability, transparency and social enquiry, and heightens the demand for increased use of participatory approaches in designing and evaluating development interventions. However, within the context of this theoretical basis, the existing compulsory associated standards for evaluating the quality of evaluations based on the PES provide limited methodological scope and coverage towards assessing the quality of evaluations of social development interventions, which exacerbated these inconsistencies in evaluation outcomes of the effectiveness of poverty-reduction interventions in Uganda. Confronted with this conundrum, the researcher makes one knowledge contribution to the methodology for conducting metaevaluations based on PES. Contrary to heightened demand for increased use of participatory approaches in designing and evaluating social development interventions based on the theoretical basis, which underpinned this study, the evidence from the analysis of the findings surprisingly revealed that a full range of stakeholders was not adequately identified and engaged in the designing and evaluation processes. Whilst stakeholder identification is not prescribed as an exclusive compulsory associated standard based on the PES by which to measure the quality of evaluations, it is empirically plausible to elevate stakeholder identification grounded in the interactive style of evaluative inquiry which is based on the assumption that those with direct vested interests in the intervention should also control the evaluation of the intervention as an additional independent compulsory associated standard under Utility Standards based on the PES when conducting metaevaluations of evaluations of not only poverty-reduction interventions, but also other social development interventions. The elevation of Stakeholder Identification (US1) as an additional independent compulsory associated standard under Utility Standards (US) based on the PES can play an important role of not only contributing towards a better resolution of plausible causes of inconsistencies in the evaluation outcomes of the effectiveness of social development interventions, but can also contribute to a better understanding of how, in practice, the identification and engagement of a full range of stakeholders enhances the promotion of the principles of accountability, transparency and participation, all of which are grounded in theories for good programme evaluation. These principles, if correctly applied, can also insulate evaluation processes of social development interventions from other causes of inconsistencies, such as bureaucratic bottlenecks and conflict of interest.
A thesis submitted to the Faculty of Commerce, Law and Management at the University of the Witwatersrand, Johannesburg in fulfillment of the requirements for the Degree of Doctor of Philosophy. 29 November 2017
Keywords: Evaluation research (Social action programs)--Uganda; Financial institutions--Uganda